A Five-Year Review of Perforated Peptic Ulcer Disease in Irrua, Nigeria. (1st June 2017) - Dongo, A. E.; Uhunmwagho, O.; Kesieme, E. B.; Eluehike, S. U.; Alufohai, E. F.
Abstract : Background . Peptic ulcer perforation is a common cause of emergency admission and surgery. This is the first study that documents the presentation and outcome of management in Irrua, Nigeria. Patients and Method . This is a prospective study of all patients operated on for perforated peptic ulcer between April 1, 2010, and March 31, 2015. A structured questionnaire containing patients' demographics, operation findings, and outcome was filled upon discharge or death. Results . There were 104 patients. 81 males and 23 females (M : F = 3.5 : 1). The age range was between 17 years and 95 years. The mean age was 48.99 years ± SD 16.1 years. The ratio of gastric to duodenal perforation was 1.88 : 1. Perforation was the first sign of peptic ulcer disease in 62 (59.6%). Pneumoperitoneum was detectable with plain radiographs in 95 (91%) patients. 72 (69.2%) had Graham's Omentopexy. Death rate was 17.3%. Conclusion . We note that gastric perforation is a far commoner disease in our environment. Perforation is often the first sign of peptic ulcer disease. We identify fasting amongst Christians as a risk factor for perforation.